Fabrication and characterization of novel electrospun nanofibers based on grass pea (Lathyrus sativus L.) protein isolate loaded with sumac (Rhus coriaria L.) extract - Marzieh Rezaei; Nasser Sedaghat; Sara Hedayati; Mohammad-Taghi Golmakani (Current Research in Food Science)
In this study, sumac extract was utilized as an active ingredient and combined with grass pea protein isolate and polyvinyl alcohol to produce novel active nanofiber mats using an electrospinning technique. First, nanofiber mats were fabricated by different ratios (100:0, 90:10, 70:30, 50:50, 30:70, 10:90, 0:100) of grass pea protein isolate and polyvinyl alcohol. The characterization of nanofiber mats revealed that the nanofibers with a polymer ratio of 50:50 had appropriate mechanical properties and presented a fibrous and uniform morphology. Therefore, the 50:50 polymer solution ratio was selected to produce active nanofibers by adding different amounts (0%, 2%, and 4% (w/v)) of sumac extract. The average diameters of nanofibers decreased from 150 ± 31 to 122 ± 25, and 105 ± 19 nm, by increasing the concentration of sumac extract. Based on the SEM results, the electrospun nanofibers exhibited a bead-free and smooth surface. The FTIR and XRD analyses indicated the presence of intermolecular hydrogen bonds between the components. The antioxidant activity of the nanofibers was confirmed by DPPH analysis and ranged between 3.33% and 68.75%. Additionally, the antimicrobial test results indicated that the nanofibers with the highest sumac concentration (4%) displayed inhibitory activity against Staphylococcus aureus, resulting in an inhibition zone of 10 mm. The optimal treatment of this study was grass pea protein isolate: polyvinyl alcohol ratio of 50:50 containing 4% sumac extract which can be used as a natural antimicrobial and antioxidant agent.